2007
DOI: 10.1364/oe.15.008805
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved confocal luminescence investigations on Reverse Proton Exchange Nd:LiNbO_3 channel waveguides

Abstract: Abstract:In this work we report on the time and spatial resolved fluorescence of Neodymium ions in LiNbO 3 channel waveguides fabricated by Reverse Proton Exchange. The analysis of the fluorescence decay curves obtained with a sub-micrometric resolution has evidenced the presence of a relevant fluorescence quenching inside the channel waveguide. From the comparison between diffusion simulations and the spatial dependence of the 4 F 3/2 fluorescence decay rate we have concluded that the observed fluorescence qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This red-shift, which was also observed in carbon ion implanted Nd:MgO:CLN planar waveguides [16], may be due to the lattice rearrangement induced by the ion implantation and the following moderate annealing, which may result in slight changes of the Nd 3+ positions in the original crystal lattice. Similar shifts towards low energy of Nd 3+ emission bands have also been observed not only in ion implanted waveguides but also in other physical systems, e.g., femto-second laser written waveguides [26], which is different from the blue shift existing in lithium niobate waveguides formed by some chemical methods (e.g., proton exchange [27]). In addition, the maximum spectral broadening (linewidth) as low as 0.2 cm -1 detected in the O + ion implanted Nd:SLN waveguide regions, also suggests that the low dose ion implantation only causes a slight increment in the lattice dis-order, which can be associated to a low density of ion implantation induced defects.…”
Section: Resultssupporting
confidence: 67%
“…This red-shift, which was also observed in carbon ion implanted Nd:MgO:CLN planar waveguides [16], may be due to the lattice rearrangement induced by the ion implantation and the following moderate annealing, which may result in slight changes of the Nd 3+ positions in the original crystal lattice. Similar shifts towards low energy of Nd 3+ emission bands have also been observed not only in ion implanted waveguides but also in other physical systems, e.g., femto-second laser written waveguides [26], which is different from the blue shift existing in lithium niobate waveguides formed by some chemical methods (e.g., proton exchange [27]). In addition, the maximum spectral broadening (linewidth) as low as 0.2 cm -1 detected in the O + ion implanted Nd:SLN waveguide regions, also suggests that the low dose ion implantation only causes a slight increment in the lattice dis-order, which can be associated to a low density of ion implantation induced defects.…”
Section: Resultssupporting
confidence: 67%
“…It can be observed that all of them are sensitive enough to reflect changes induced by the incorporation of Zn 2+ ions into the substrate. The sensitivity of this particular Tm 3+ transition to local distortions seems to be higher than that reported for the 4 F 3/2 -4 I 9/2 transition of Nd 3+ ions [11][12][13]. Both, intensity and bandwidth change in the same region, and those changes are detected up to a depth around 5 mm, coincident with the region where Zn 2+ in-diffusion takes place (the dark grey region limited by a dotted line in Fig.…”
Section: Resultsmentioning
confidence: 59%
“…Direct evaluation has also been performed along the last few years using site-selective and guided modes spectroscopy [7][8][9] that provide detailed spectral information although, due to the fact that it is extracted from the analysis of propagated light, it is inevitably averaged over the whole length of the waveguide. Confocal micro-luminescence applied to the characterization of waveguides has recently appeared as a tool that provides direct and precise information on the local properties of the material, being especially interesting since it allows the 3D plotting of different physical magnitudes, and therefore the whole visualization of the micro-structural modifications associated to waveguides fabrication [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, channel or ridge waveguides are more widely used than planar waveguides, such as switches, splitters and amplifiers, due to the stronger spatial confinement of light, reaching higher optical intensities within more compact scales [14,15]. There are many methods to fabricate waveguides, such as metal ion indiffusion, ion implantation, proton exchange, direct femtosecond laser writing or the combination of the above-mentioned methods [16][17][18][19]. The ion implantation technique is an excellent method for waveguide fabrication due to the controllable number, energy, temperature and range of the implanted ions.…”
Section: Introductionmentioning
confidence: 99%